High frequency of autoimmune thyroiditis in euthyroid girls with premature adrenarche - Kyritsi, Eleni Magdalini; Vasilakis, Ioannis-Anargyros; Kosteria, Ioanna; Mantzou, Aimilia; Gryparis, Alexandros; Kassi, Eva; Kaltsas, Gregory; Kanaka-Gantenbein, Christina (Frontiers in Pediatrics, 2023)
Objective: The purpose of this study was to investigate the frequency of autoimmune thyroiditis (AT) among euthyroid prepubertal girls presenting with premature adrenarche (PA). We also aimed to identify the clinical, metabolic, and endocrine profile of girls with AT and concurrent PA and compare them to girls with AT without PA, PA alone and healthy controls. Methods: Ninety-one prepubertal girls aged 5-10 years, who attended our department for AT, PA and normal variants of growth and puberty were recruited for the study: 73 girls had PA, 6 AT without PA and 12 were referred for investigation of growth. All girls underwent clinical examination, detailed biochemical and hormonal screen. Standard dose Synachten stimulation test (SDSST) and oral glucose tolerance test (OGTT) were performed in all girls with PA. The whole study population was divided in 4 groups: Group PA-/AT+ included 6 girls with AT without PA; Group PA+/AT- PA subjects without AT; Group PA+/AT+ girls with PA and concomitant AT; Group PA-/AT- twelve healthy girls without PA nor AT (controls). Results: Among 73 girls presenting with PA 19 had AT (26%). BMI, systolic blood pressure (SBP) and the presence of goiter significantly differed between the four groups (p=0.016, p=0.022 and p<0.001, respectively). When comparing hormonal parameters among the four groups significant differences were found in leptin (p=0.007), TSH (p=0.044), anti-TPO (p=0.002), anti-TG (p=0.044), IGF-BP1 (p=0.006), Δ4-Α (p=0.01), DHEA-S (p=<0.001), IGF-1 (p=0.012) and IGF-BP3 (p=0.049) levels. TSH levels were significantly higher in Group PA+/AT+ compared to PA+/AT- and PA-/AT- (p=0.043 and p=0.016, respectively). Moreover, girls with AT (Groups PA-/AT+ and PA+/AT+) had higher TSH levels than those in Group PA+/AT- (p=0.025). Girls in Group PA+/AT+ showed higher cortisol response at 60 min post-SDSST than girls in Group PA+/AT- (p=0.035). During the OGTT, insulin concentrations at 60 min were significantly higher in Group PA+/AT+ compared to Group PA+/AT- (p=0.042). Conclusion: A high frequency of AT among euthyroid prepubertal girls with PA was observed. The combination of PA with AT even in euthyroid state may be associated with a greater degree of insulin resistance, than PA alone.